Perencanaan Sumber Daya Manusia, Recruitment dan Job Analysis Berpengaruh Terhadap Kinerja Karyawan PD. Gunasalma Kawali Kabupaten Ciamis - Nurul Hasanah; Irma Bastaman; Nurdiana Mulyantini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study focuses on the analysis of Human Resource Planning, Recruitment and Job Analysis Affecting Employee Performance of PD. Gunasalma Kawali, Ciamis Regency. The formulation of the problem in this study is to analyze the effect of Recruitment and Job Analysis on employee performance of PD. Gunasalma Kawali, Ciamis Regency. The purpose of this study is to determine the Human Resource planning of PD. Gunasalma Kawali, Ciamis Regency employees, to find out the Recruitment of PD. Gunasalma Kawali, Ciamis Regency employees, to find out the Job Analysis of PD. Gunasalma Kawali, Ciamis Regency employees and to find out the effect of Human Resource planning, Recruitment and Job Analysis on Employee Performance of PD. Gunasalma Kawali, Ciamis Regency. Respondents in this study were 50 employees of PD. Gunasalma Kawali, Ciamis Regency. The research method used is to use a quantitative research method. Then the data was analyzed using Multiple Regression Analysis, Simultaneous Test, Partial Test and Determination Coefficient. The results of this study indicate: That the three variables affect employee performance. For the Human Resource Planning variable, the b1 value in the model is 0.893. For the Recruitment variable, the b2 value in the model is 0.742. For the Job Analysis variable, the b3 value in the model is 0.697. So the influence of HR Planning, Recruitment and Job Analysis on Employee Performance in the model is 75.6%, and 24.4% is influenced by other factors or causes.